Strategies to Improve Participation of Pelagio Arabica Coffee Farmers in Village Educational Tourism Development During the Launch Phase Case Study in Sukaalilah Village, Sukaresmi District - Asyim Burhani; Mulyaningsih; Emil Al-Fath Ilmawan; Yusuf Musyaffa (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
Sukalilah Village (Sukaresmi District, Garut Regency) combines favorable highland agroclimate for Arabica coffee with growing prospects for agricultural educational tourism. Yet farmer participation in planning, implementation, and management remains limited, constraining product coherence and long-term viability. This article aims to formulate participation-enhancement strategies for the launch phase of coffee edutourism, drawing on community participation theory, farmer empowerment, and edutourism principles. Using a qualitative descriptive design, a literature review was conducted across peer-reviewed journals, textbooks, government reports, and policy documents, followed by thematic-analytic synthesis. The findings suggest that participation can be strengthened through capacity building (guiding, interpretation, service standards), institutional reinforcement of farmer groups, multi-stakeholder collaboration, diversified learning packages from farm to cup, digital tools for promotion and booking, and simple indicator-based monitoring and evaluation. These strategies are expected to improve farmer welfare, broaden village economic benefits, and consolidate Sukalilah’s identity as an inclusive and sustainable coffee learning destination in practice. Keywords: Arabica coffee; Educational tourism; Farmer participation.